O ensino de ciências na formação dos professores: limites, desafios e possibilidades no curso de pedagogia - Rodrigues, Cintia Cavalcante (2017)
The research entitled The Science Education In Teacher Training: limits, challenges and possibilities in the course of pedagogy was developed in the Master's Degree in Science Education and Teaching in the Amazon from the Universidade do Estado do Amazonas (UEA) in which the objective was to understand the limits, challenges and possibilities of Teaching Science in the Pedagogy Course. The training of teachers in Science Teaching has been the subject of discussions and debates regarding the initial years of Elementary Education. This curricular component directed to the students of the initial years is formed by professionals trained in the Degree of Pedagogy in this sense it is necessary to understand the initial formation of these future teachers. The theoretical basis of this research was based on the epistemology of Gaston Bachelard with the formation of the scientific spirit. The analysis’ categories were organized in: Conceptions of Science and Teaching of Sciences, Teaching of Sciences as a curricular component and Teaching of Sciences in the Pedagogy’s Course. In methodological procedures we work on a qualitative research approach. The kind of research presented is the participant with the observation techniques of the Teaching Methodology and Learning Sciences Nature, semi-structured interviews with the teacher of the discipline, coordinator of the Course and Focal Group with the finalist students of Pedagogy. We work on Data analysis, from Laurence Bardin with the content analysis triangulating the different data collected in a dialectical perspective. The analysis results showed the limits in the conceptions that were now restrictive in relation to Science Teaching, limiting it to a single curricular component, or they saw it in a sphere of investigation, reflection and as solutions element of social problems evidencing the absence of public policies that corroborate with the tripod: Teaching, Research and Extension. These limits constitute challenges to be overcome by the collective that constitutes this formative process of pedagogy’s students who need to develop a scientific, critical and reflective spirit. Regarding the process possibilities, we highlight the interdisciplinarity and the struggle for public education policies for teachers in Science Teaching. Therefore, we understand this knowledge area has limits, challenges and possibilities that go far beyond a curricular component, opening up paths to other questions which permeate the Curriculum of Pedagogy and, consequently, Science Teaching, understanding that we believe that a researcher teacher, reflective and critical is not born ready, but can be developed from its formation